2005
DOI: 10.1007/s10722-005-0005-x
|View full text |Cite
|
Sign up to set email alerts
|

Intra-specific DNA polymorphism in pineapple (Ananas comosus (L.) Merr.) assessed by AFLP markers

Abstract: Pineapple (Ananas comosus (L.) Merr.) cultivars, often derived from somatic mutations, are propagated vegetatively. It has been suggested by isozyme data that there is little genetic variation among Smooth Cayenne cultivars. A thorough investigation of the genetic variation within the cultivated species Ananas comosus, particularly among commercial cultivars, will provide critical information needed for crop improvement and cultivar protection. One-hundred and forty-eight accessions of A. comosus and 14 access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 22 publications
3
16
0
2
Order By: Relevance
“…Similar results were reported by other studies that used DNA marker analysis to classify pineapple cultivars (Kato et al, 2005;Shoda et al, 2012). Collins (1960) showed that whether the outside edge of the leaf is spiny or lack spines is controlled by a single gene.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Similar results were reported by other studies that used DNA marker analysis to classify pineapple cultivars (Kato et al, 2005;Shoda et al, 2012). Collins (1960) showed that whether the outside edge of the leaf is spiny or lack spines is controlled by a single gene.…”
Section: Discussionsupporting
confidence: 82%
“…According to the genetic distance derived from SSR markers of 27 pineapple cultivars in the study, the results show that there is a high degree of genetic variation among pineapple cultivars in Taiwan. This variation has also been revealed in DNA studies of pineapple cultivars by AFLP markers (Kato et al, 2005) and SSR markers (Kinsuat and Kumar, 2007). It may result from the combination of self-incompatibility, high levels of somatic mutation, and intraspecific hybridization in pineapple (Kato et al, 2005).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…For the collection to be more representative of the broad spectrum of pineapple germplasm, it should be enriched with more cultivated and non-cultivated varieties since most of genotypes in this collection are Red Spanish or Cayenne´s cultivars. Other collections previously characterized with morphological descriptors (Leal et al 1986, Ferreira and Cabral 1993, Duval et al 1996, such as those from Brazil, Martinique and Hawaii or with molecular markers such as the Brazilian (Duval et al 2001) and the Hawaiian collections (Kato et al 2004) showed more diversity.…”
Section: Resultsmentioning
confidence: 91%
“…The technique has also been employed to identify varieties in pineapple (Leal et al ARTICLE EY Paz et al 1986) and carry out classical genetic mapping studies (Carlier et al 2004). Kato et al (2004), Paz et al (2005) and Tapia proved its suitability for germplasm evaluation.…”
Section: Introductionmentioning
confidence: 99%